Clinical Communication in Diagnostic Imaging Studies - Pirnejad, H.; Niazkhani, Z.; Bal, R. (Applied Clinical Informatics, 2013)
Objective: To examine how and why the quality of clinical communication between radiologists and referring physicians was changed in the inpatient imaging process after implementation of a hospital information system (HIS).Methods: A mixed-method study of the chest X-ray (CXR) requests and reports, and their involved processes within a pre- and post-HIS implementation setting.Results: Documentation of patient age, patient ward, and name and signature of requesting physician decreased significantly in post-HIS CXR requests (P<0.05). However, documentation of requested position and technique increased significantly (P<0.05). In post-HIS CXR reports, documentation of patient age, patient chart number, urgent/normal status of requisition, position and technique of CXR, name of referring physician, and date of request were increased significantly (P<0.05). However, documentation of discussion for important findings was decreased significantly (P<0.05). The mean number of words in the body text of post-HIS reports was increased significantly (18.65 vs. 16.3, P = 0.00).Our qualitative findings highlighted that involving nursing and radiology staff in the communication loop between physicians and radiologists after the implementation resulted in extra steps in the workflow and more workload for them. To cope with the new workload, they adopted different workarounds that could explain the results seen in the quantitative study.Conclusion: The HIS improved communication of administrative and identification information but did not improve communication of clinically relevant information. The reason was traced to the complications that the inappropriate implementation of the system brought to clinical workflow and communication loop.Citation: Pirnejad H, Niazkhania Z, Bal R. Clinical communication in diagnosticimaging studies - mixedmethod study of pre- and post-implementation of a hospital information system. Appl Clin Inf 2013; 4: 541–555http://dx.doi.org/10.4338/ACI-2013-06-RA-0042
Keywords: Communication; hospital information system; chest X-ray; workflow; patient safety